ULUL ALBAB: POTRET REVOLUSIONER MENTAL DALAM PERSPEKTIF AL-QUR’AN - Nadra Ulfah (EL-ADABI : Jurnal Studi Islam, 2022)
The mental revolution is President Joko Widodo's statement to make Indonesian people have good character and live in security and peace. Al-Qur'an as a book of instructions and a source of knowledge explains the process of mental revolution. The mental revolution in the Qur'an is carried out by combining the potential that exists in humans, namely intellectual, emotional and spiritual potential. In QS Ali Imron verses 190-191 a human being who can combine these three potentials is called "ulul albab". Thus, how the process of mental revolution through the Al-Qur'an approach is discussed in this writing.